Environment Overuse in Indonesia: The Optimization Based on Regional and International Law Perspective - Desia Banjarani; Joni Emirzon; Iza Rumesten RS; Artha Febriansyah; Ikhsan Setiawan (Kertha Patrika, 2025)
The purposes of this research is to identify and analyzed environmental management regulated according to international and Indonesia law. Also to proposed the optimization land conversion regulations to overcome exploitation. The research method used in this research is the library search method, namely by studying various legal books, a collection of laws and regulations, legal articles, the internet and other written sources. The results of the study show how the regulation of international law for the protection of the environment needs to be considered for its sustainability. From this research, it can be concluded that international law regulation on environmental utilization must have an appropriate spatial planning by taking into account the sustainability of the environment itself.